(untitled) (Per Musi, 2012)
This study aimed at developing an inventory to assess social and physical environments determinants that influence the healthy behavior related to prevention of occupational injuries in musicians. The process of constructing the inventory is based on the guidelines for construction of psychological instruments by PASQUALI (1999) and the concept formulated by the ecological perspective.